“Relevance Of Learning Outcome -Based CurriculumFramework For Effective Implementation Of NEP-20’’ (International Journal of Food and Nutritional Sciences, 2023)
This research paper aims to explorer the relevance and effectiveness of Learning outcomebased curriculum Framework in undergraduate in the Indian context. Learning Outcome-Based Curriculum Framework(LOCF) is an approach that focuses on defining clear and measurable learning outcomes for students, aligning teaching and evaluation with these outcomes, and achieved outcomes. The paper will examine the rationale behind adopting OBC for effective implementation of NEP -20(National Education Policy -India) its benefits, challenges faced during its implementation, and the impact it has on student learning and overall educational outcomes in India. The study is carried out through a survey. The observations areencouraging, the concept of OBE in terms of curriculum design, delivery, assessment, evaluation and reflection is penetrating inthe under graduate programs in India but still trainings in certain aspects are required.